The Effect of E-Customer Value and Internal Factors on E-Trust, E-Satisfaction, and E-Repurchase Intention in Online Marketplaces - Sirajudin Sirajudin; Nasrulhak Akkas; Sarifuddin T (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
The development of internet technology has transformed consumer behavior, shifting society toward online shopping activities. This lifestyle change is reflected in the increasing demand for goods and services that can be accessed quickly and conveniently through digital platforms. This study aims to analyze the effect of e-customer value and internal factors on e-trust, e-satisfaction, and e-repurchase intention, as well as to examine the mediating role of e-trust and e-satisfaction in online repurchase behavior. This research uses a quantitative approach with Structural Equation Modeling (SEM) based on a sequential explanatory design. Data were collected through a survey of e-commerce users and analyzed to test the relationships among the variables. The results show that e-customer value and internal factors have a positive effect on e-trust, e-satisfaction, and e-repurchase intention. In addition, e-trust and e-satisfaction also have a positive effect on e-repurchase intention. The mediation analysis reveals that e-trust mediates the relationship between e-customer value and e-repurchase intention, while e-satisfaction mediates the relationship between internal factors and e-repurchase intention. This study contributes to the development of consumer behavior literature in online shopping by highlighting the importance of customer value, internal factors, and mediating psychological mechanisms in shaping repurchase intention in e-commerce environments.